أحكام الشارة المميزة في القانون الدولي الإنساني - المالكي هادي نعيم (Journal of Legal Sciences, 2020)
Thousands of victims of disasters, wars and armed conflicts Found in the emblems of the Red Cross and Red Crescent as a safe haven that protects these victims from violence, and extend a helping hand in the midst of adversity, and a symbol of humanity. However, these symbols which used to protect members of the military medical services during the wars, and a hallmark of the members of the Red Crescent and Red Cross in peace, were at the same time a reason to raise real difficulties because of the multiplicity of these badges, as the significance of religious insignia to create a situation of bias of Islamic and Christian countries at the expense of other religions. This re-search, aim to study and analyze the current status quo and offer the project - drafted, proposed by the states and was adopted by the movement in order to reach to a comprehensive solution to the question of the emblem.